Macroscopic production of spin-polarised hydrogen atoms from the IR-excitation and photodissociation of molecular beams. (17th January 2022) - Kannis, C. S.; Suarez, J.; Rakitzis, T. P.
Abstract : We describe methods for the production of spin-polarised H and D atoms from the IR-excitation and photodissociation of molecular beams of HBr, HI, and NH3 isotopes, including optical excitation schemes with partial hyperfine resolution. We discuss the extent to which the production rates may approach the IR-laser production rates of 10 21 photons s − 1, and how the production rates of conventional methods of ∼ 10 17 s − 1 may be surpassed significantly. GRAPHICAL ABSTRACT: UF0001